Research on the Evaluation of the Development Level of New Quality Productive Forces in China’s Agriculture - Mengyu Hao; Yanming Xie; Qinglin Chen; Zhande Zhou (Journal of Frontier in Economic and Management Research, 2025)
Cultivating new agricultural productive forces is an inherent requirement and a key focus for promoting high-quality agricultural development and building a strong agricultural country. Based on panel data from 30 provinces and cities in mainland China from 2012 to 2022, the entropy method, Dagum Gini coefficient, and Moran’s I were used to study the development level of new agricultural productive forces. The results show that: first, the development level of China’s new agricultural productive forces has steadily improved, and at the regional level, it shows a decreasing trend in the order of the eastern, central, western, and northeastern regions; second, the degree of inequality in the development of China’s new agricultural productive forces has continued to expand, and the inter-regional gap is the main reason for the unbalanced development; third, the development of China’s new agricultural productive forces has a positive spatial autocorrelation in space, with a concentrated distribution. Accordingly, policy recommendations are put forward from the perspective of the overall development level and regional difference characteristics of new agricultural productive forces.